CLINICAL EVALUATION OF MANAGEMENT AND PREVALENCE OF TYPE TWO DIABETES MELLITUS COMPLICATIONS IN SOUTH INDIAN POPULATION - P, Geetha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was aimed to assess the prevalence of complications and to assess the targets achieved during the management of diabetes mellitus type 2. Methods: The study was prospective and conducted out in a diabetes center, Chennai, ethical approval was obtained from the Institutional Ethics Committee, case records of the 300 patients diagnosed with type 2 diabetes mellitus and its complications were monitored during March 2017–April 2018. Major result actions are body weight, height, body mass index (BMI), blood pressure, fasting blood sugar (FBS), post-prandial blood sugar (PPBS) levels, glycosylated hemoglobin, serum lipids, and presence of complications of diabetes. Comparison of the average of various biochemical parameters was made in patients with and no diabetic complications. Results: The average age of 300 patients was found to be 55.006±13.04. The average BMI was 27.10±12.81 kg/m2. The average duration of diabetes was 10.48±7.53. The average of systolic (SBP) and diastolic blood pressure was 137±20.88 and 79.95±11.81. The mean glycated hemoglobin, FBS, PPBS, low-density lipoprotein, high-density lipoprotein, and triglyceride, and total cholesterol were found to be 8.5±3.99, 148.85±55.64 mg/dl, 200.98±72.63 mg/dl, 88.06±19.46 mg/dl, 36.20±8.27 mg/dl, 141.22±60.15 mg/dl, and 144.45±29.03 mg/dl, respectively. Among the microvascular complications; neuropathy, nephropathy, and retinopathy were documented in 8.33%, 23.66%, and 17.33% of patients, respectively. The prevalence of peripheral artery disease was 20.66%. Conclusion: The prevalence of diabetic complications is significantly increased with patients age, duration, SBP, low-density lipoprotein, total cholesterol, and post-prandial blood sugar levels. Knowledge concerning the supervision of target blood pressure and lipid parameters is need further than the glycemic manage among diabetes patients type two.